Nontuberculous Mycobacteria on Ready-to-Eat, Raw and Frozen Fruits and Vegetables - Dziedzinska, Radka; Makovcova, Jitka; Kaevska, Marija; Slany, Michal; Babak, Vladimir; Moravkova, Monika (Journal of food protection, 2016)
The consumption of fruits and vegetables is increasing worldwide because of the positive impact of these foods on human health. Ready-to-eat, raw whole, and frozen fruits and vegetables were purchased from markets and examined for the presence of nontuberculous mycobacteria (NTM) using culture, real-time PCR (qPCR), and sequencing. Using qPCR, Mycobacterium sp. at 10(0) to 10(4) ge/g (genome equivalents per gram) was found in almost all of the 178 samples; members of the M. avium complex were found only sporadically. Culture and sequencing revealed the presence of 22 viable NTM isolates in 17 samples. In addition to NTM commonly found in the environment, several rarely described isolates of viable NTM were recovered. The presence of Mycobacterium shigaense, which has been previously isolated only from human patients, was found in lettuce, the first time that this species has been found in an environmental sample. Mycobacterium parmense, Mycobacterium palustre, and Mycobacterium llatzerense, which have been previously isolated from human patients and occasionally from soil and water, were recovered from leafy green vegetables. Strawberries and cut salad mixes contained Mycobacterium algericum, Mycobacterium fallax, and Mycobacterium minnesotense. NTM are primarily nonpathogenic. However, consumption of fruits or vegetables contaminated with NTM could represent a health risk for immunocompromised people, children, and the elderly.
Keywords: Environment; zelenina; životní prostředí; ovoce; lidé; netuberkulózní mykobakterie; Vegetables; Nontuberculous Mycobacteria; Fruit; Humans